1999
DOI: 10.1259/bjr.72.855.10396217
|View full text |Cite
|
Sign up to set email alerts
|

CT findings in involvement of the paranasal sinuses by lepromatous leprosy.

Abstract: The role of nasal infection in the transmission of leprosy has been extensively studied. Leprosy can affect the paranasal sinuses due to mucosal continuity and bacillaemia. This prospective study was performed on 25 untreated patients with lepromatous leprosy. 5 mm contiguous axial and coronal CT sections of paranasal sinuses, on soft tissue and bone windows, were obtained in all patients. Each sinus was examined for mucosal thickening, soft tissue densities and bony outlines. Representative biopsies were take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 2 publications
0
12
0
5
Order By: Relevance
“…2,7,8 On the other hand, a previous study of treated lepromatous leprosy patients found septal perforation in 47.3 per cent (18 of 38), suggesting that, in cases of persistent infection, cartilage destruction may continue even after the treatment of leprosy. Lepromatous leprosy is the severest type of leprosy, so we presumed that massive chronic granulomatous infection had caused these scar formations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…2,7,8 On the other hand, a previous study of treated lepromatous leprosy patients found septal perforation in 47.3 per cent (18 of 38), suggesting that, in cases of persistent infection, cartilage destruction may continue even after the treatment of leprosy. Lepromatous leprosy is the severest type of leprosy, so we presumed that massive chronic granulomatous infection had caused these scar formations.…”
Section: Discussionmentioning
confidence: 94%
“…7,8 Similarly, the ethmoidal sinuses have been reported to be the most commonly involved sinuses (55.2 per cent) in treated lepromatous leprosy patients; furthermore, 33.3 per cent of these patients have had persistent acidfast bacilli infection. Ex-leprosy patients are sometimes exposed to antibiotics for management of the complications of leprosy.…”
Section: Discussionmentioning
confidence: 99%
“…Ethmoidal sinuses are affected in 33% to 80% of patients, maxillary sinuses in 48% to 55%, sphenoid sinuses in 12% to 20%, and the frontal sinuses in 5% to 30%. 8 The diagnosis of leproma in the nasal cavity is confirmed by histopathology. Hematoxylin and eosin stain reveals infiltration of foamy histiocytes, plasma cells, and neutrophil.…”
Section: Discussionmentioning
confidence: 94%
“…10 Depending upon the host immune response, nasal symptoms of leprosy may include epistaxis, gross nasal deformity and destruction. Patient may complain of anosmia and nasal obstruction.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…10,11 This clinical report of a case of secondary atrophic rhinitis with Hansen's disease is aimed at showing the nasal finding in leprosy along with its treatment and reconstruction of the nose.…”
mentioning
confidence: 99%